Efficient Light Harvesting with Micropatterned 3D Pyramidal Photoanodes in Dye‐Sensitized Solar Cells. (2nd May 2013) - Wooh, Sanghyuk; Yoon, Hyunsik; Jung, Jae‐Hyun; Lee, Yong‐Gun; Koh, Jai Hyun; Lee, Byoungho; Kang, Yong Soo; Char, Kookheon
<x xml:space="preserve">Abstract</x> 3D TiO2 photoanodes in dye‐sensitized solar cells (DSCs) are fabricated by the soft lithographic technique for efficient light trapping. An extended strategy to the construction of randomized pyramid structure is developed by the conventional wet‐etching of a silicon wafer for low‐cost fabrication. Moreover, the futher enhancement of light absorption resulting in photocurrent increase is achieved by combining the 3D photoanode with a conventional scattering layer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>